Online Collaborative Discourse jako forma wsparcia uczniów z trudnościami w uczeniu się matematyki - Hatoum , Maha Abu (Studia Edukacyjne, 2020)
The present research study was carried out in an online learning environment in a small group of eighth-grade students. The research proposes a learning framework that relies on collaborative mathematical discourse with the intention to promote the reasoning ability of students with difficulties in mathematics. The aim of mathematical discourse is the reciprocal building of the ability of the learner with difficulties to provide explanations during the discourse between the learner and his peers and between the learner and the teacher. This type of learning was found to be effective, and the communicational continuum between the learner and the material and between the learner and the group is preserved. The learning process built on authentic mathematical tasks strengthened the learners’ ability to create communication among themselves. The discourse encouraged the development of mathematical thinking abilities among the learners with difficulties, such as posing arguments and drawing conclusions while explaining and justifying these arguments. The mathematical discourse also encouraged students to choose and to monitor the form and processes of their thinking and increased their problem-solving ability.